Intravenous glycyrrhizin as a rescue therapy in a patient with latent hepatitis B virus reactivation and acute severe decompensation induced by chemotherapy with rituximab. Issue 2 (8th April 2019) - Wang, Su‐Hung; Sheu, Ming‐Jen; Kuo, Hsing‐Tao; Lin, Ching‐Yih; Sun, Chi‐Shu; Feng, I‐Che
Abstract : Latent hepatitis B virus (HBV) reactivation related to rituximab use is associated with an increase in morbidity and mortality. We report a case of latent HBV reactivation with decompensated hepatitis that occurred 10 months after the completion of rituximab therapy. Initially, the patient's condition deteriorated, even during combination antiviral drug therapy (tenofovir plus entecavir). However, it dramatically improved after treatment with intravenous Stronger Neo Minophagen C (SNMC). Glycyrrhizin is the main component of SNMC, which plays a role inbridging therapy to allow the efficiency of antiviral drugs to develop. In addition, prolonged use of the antiviral drug after the completion of rituximab and chemotherapy should be considered to extend beyond 6 months, which is currently advised by the National Health Insurance in Taiwan.